Multidimensional Treatment Foster Care for Adolescents in English care: randomised trial and observational cohort evaluation. (March 2014) - Green, J. M.; Biehal, N.; Roberts, C.; Dixon, J.; Kay, C.; Parry, E.; Rothwell, J.; Roby, A.; Kapadia, D.; Scott, S.; Sinclair, I.
Abstract : Background: Children in care often have poor outcomes. There is a lack of evaluative research into intervention options. Aims: To examine the efficacy of Multidimensional Treatment Foster Care for Adolescents (MTFC-A) compared with usual care for young people at risk in foster care in England. Method: A two-arm single (assessor) blinded randomised controlled trial (RCT) embedded within an observational quasi-experimental case–control study involving 219 young people aged 11–16 years (trial registration: ISRCTN 68038570). The primary outcome was the Child Global Assessment Scale (CGAS). Secondary outcomes were ratings of educational attendance, achievement and rate of offending. Results: The MTFC-A group showed a non-significant improvement in CGAS outcome in both the randomised cohort ( n = 34, adjusted mean difference 1.3, 95% CI −7.1 to 9.7, P = 0.75) and in the trimmed observational cohort ( n = 185, adjusted mean difference 0.95, 95% CI −2.38 to 4.29, P = 0.57). No significant effects were seen in secondary outcomes. There was a possible differential effect of the intervention according to antisocial behaviour. Conclusions: There was no evidence that the use of MTFC-A resulted in better outcomes than usual care. The intervention may be more beneficial for young people with antisocial behaviour but less beneficial than usual treatment for those without.